2002
DOI: 10.1016/s1097-2765(02)00791-8
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Activation by Enhancer-Dependent and -Independent Loading of Activator and Coactivator Complexes

Abstract: Activation of the pDbeta1 promoter at the TCRbeta locus requires a functional distal enhancer, Ebeta. Here, we have analyzed the mechanism of promoter activation in thymocytes from mice containing or lacking Ebeta. We found that pDbeta1 shows a complex profile of transcription factor and chromatin remodeling complex occupancy even at Ebeta(-) alleles. The presence of Ebeta, however, results in a few specific changes in factor occupancy at the promoter. These differences correlate with localized alterations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 36 publications
13
73
3
Order By: Relevance
“…Our results implicating a primary function of the LCR downstream of PIC assembly contrast with a recent report showing that the endogenous 3Ј TCR␤ enhancer (E␤) acts to modify chromatin and in the recruitment of pol II, TBP, and transactivators at the upstream pD␤1 promoter (Spicuglia et al 2002). Clearly, these differences could be due to different technical approaches (e.g., ChIP procedures).…”
Section: Relationship Between Expression Levels and Pic Assemblycontrasting
confidence: 99%
“…Our results implicating a primary function of the LCR downstream of PIC assembly contrast with a recent report showing that the endogenous 3Ј TCR␤ enhancer (E␤) acts to modify chromatin and in the recruitment of pol II, TBP, and transactivators at the upstream pD␤1 promoter (Spicuglia et al 2002). Clearly, these differences could be due to different technical approaches (e.g., ChIP procedures).…”
Section: Relationship Between Expression Levels and Pic Assemblycontrasting
confidence: 99%
“…BRM and BRG1 play important roles in the immune system SWI/SNF plays an important role in immune responses, T-cell development and recombination events (Golding et al, 1999;Agalioti et al, 2000;Kwon et al, 2000;Spicuglia et al, 2002;Morshead et al, 2003). The SWI/ SNF complexes have been shown to remodel chromatin in such a way as to drive consecutive developmental transitions in T cells in response to external stimuli.…”
Section: Brm and Brg1 Control The Expression Of Genes That Are Involvmentioning
confidence: 99%
“…Variable-diversity-joining (V(D)J) recombination has also been shown to be mediated by SWI/SNF. BRG1 stimulates in vitro recombination of chromatin and is also bound to regions in the T-cell receptor (TCR) and immunoglobulin loci that take part in recombination events (Golding et al, 1999;Kwon et al, 2000;Spicuglia et al, 2002;Morshead et al, 2003;Patenge et al, 2004). More recent studies have shown SWI/SNF to be fundamental to the promoter-directed assembly of TCR-b (TCRB) genes (Osipovich et al, 2007); SWI/ SNF is recruited to promoters and then facilitates recombination by exposing segments of genomic DNA to V(D)J recombinase.…”
Section: Brm and Brg1 Control The Expression Of Genes That Are Involvmentioning
confidence: 99%
“…This being the case, the length of the window might have been overestimated. Alternatively, the values may cover additional events including the local epigenetic changes that in effect trigger this first rearrangement step (64,65); prompt Db-Jb transitions would have no biological reality (with little impact on our data because this option only bears on tiny cell percentages). In the future, thorough examination of Db-Jb recombination in DN cells, under single-cell assay conditions, may be necessary to close this debate.…”
Section: Discussionmentioning
confidence: 99%